Management of post cardiac arrest - Mat Nor, Mohd. Basri (2011)
The 2010 ACLS Guidelines recommend a combination of goal-oriented interventions provided by an experienced multidisciplinary team for all cardiac arrest patients with return of spontaneous circulation (ROSC). Important objectives of post-cardiac arrest are: • Optimizing cardiopulmonary function and perfusion of vital organs • Managing acute coronary syndromes that includes acute cardiovascular interventions • Implementing therapeutic hypothermia • Implementing strategies to prevent and manage organ system dysfunction. Attention should be directed to treating the precipitating cause of cardiac arrest after the ROSC. It is helpful to review the H’s and T’s mnemonic to recall factors that may contribute to cardiac arrest or complicate resuscitation or post-resuscitation care. The induction of mild therapeutic hypothermia (target temperature 32 to 34ºC) is beneficial in patients successfully resuscitated after a cardiac arrest. Induced hypothermia after successful resuscitation leads to one additional patient with intact neurological outcome for every 6 patients treated. One good randomized trial (HACA study group) and pseudo randomized trial (Australian study, Bernard et al) reported improved neurologically intact survival to hospital discharge when comatose patients without of hospital cardiac arrest (VF) were cooled for 12 or 24 hours. No RCTs have compared outcome between hypothermia and normothermia for non-VF cardiac arrest. Early prognostication of neurological outcome in comatose cardiac arrest survivors is an essential component of post cardiac arrest care. Poor outcome is defined as death, persistent unresponsiveness, or the inability to undertake independent activities after 6 months. Certain clinical criteria have been demonstrated to be reliable in identifying individuals with a very poor prognosis. Absent pupillary or corneal reflexes, or absent or only extensor motor responses at three days after cardiac arrest are invariably associated with a poor outcome. Potential confounding factors in the clinical assessment of patients in hypoxic ischemic coma include acute metabolic derangements (e.g. renal failure, liver failure and shock), the administration of sedative or neuromuscular agents, and induced-hypothermia therapy.